Marine ecotourism in Brazil: from origins to implementation feasibility - Pedrini, Alexandre de Gusmão (Revista Brasileira de Ecoturismo (RBEcotur), 2018)
This literature review aims at analyzing and reflecting upon the genesis of marine ecotourism in Brazil from an environmental education perspective. It covers the study of two representative cases of marine ecotourism along the Brazilian coast, which develop direct benthic-community watching – one on rocky shores (EcoTurisMar Project) and another on coral reefs (ProMar Project). ProMar, implemented in Environmental Protection Area of Tinharé and Boipeba Islands, sells products by US 16 each and generates about US 430 every ten days. Main constraints to sustainable marine ecotourism identified by the study were: a) lack of governmental funding for the development of sustainable marine ecotouristic products; b) absence of laws making it mandatory for tour operators to offer sustainable marine ecotouristic products inside and around protected areas; c) higher costs of marine ecotouristic products in comparison with mainstream touristic products; d) local traders’ lack of interest in undertaking sustainable marine ecotouristic products; e) funding and general choice for environmentally damaging mainstream touristic products; f) lack of low-interest public funding for community-based ecotouristic enterprises; g) governmental divestment from public universities ¬– and thus from faculty’s projects; h) dismantling of socioenvironmental governmental agencies liable for control and surveillance, especially in relation to marine fauna-watching ecotourism. Results suggest the urgency of an in loco inventory of marine ecotourism activities in Brazil. By taking into consideration the input from several stakeholders engaged in touristic trade, sustainable marine ecotourism can be implemented in a way that comprehends all kinds of sustainability Ecoturismo marinho no Brasil: das origens à viabilidade de implementação Esse artigo de revisão sintetiza e reflete criticamente sobre a gênese do ecoturismo marinho no Brasil, sob a perspectiva da educação ambiental. O trabalho se concentra em dois estudos de casos emblemáticos de observação da comunidade bentônica marinha costeira. Um caso é o Projeto EcoTurisMar desenvolvido para observação da comunidade bentônica de costões rochosos marinhos no sudeste e o outro caso é o Projeto ProMar realizado para reconhecimento da vida marinha dos recifes de coral no nordeste brasileiro. O Projeto que mais avançou foi o ProMar implementado na Área de Proteção Ambiental das Ilhas de Tinharé e Boipeba no Estado da Bahia. Ele vende cada produto por US16 e acumula US430 a cada 10 dias. As principais dificuldades identificadas para a sustentabilidade do ecoturismo marinho local são: a) falta de financiamento inicial do governo local para o desenvolvimento de produtos ecoturísticos; b) ausência de legislação que obrigue às operadoras de turismo locais a oferecer produtos de ecoturismo marinho sustentáveis nos limites das áreas protegidas; c) custo mais alto dos produtos de ecoturismo marinho de base local quando comparados com os do turismo marinho massificados e insustentáveis; d) desinteresse dos empresários de turismo local em desenvolver e vender o ecoturismo marinho sustentável local; e) escolha do público pelo turismo marinho que danifica a biota local; f) desinteresse da população local em criar empresas de ecoturismo; g) desinvestimento governamental nas universidades públicas e consequentemente falta de dinheiro para desenvolvimento de projetos universitários como os de ecoturismo marinho; h) desconstrução das agências governamentais de fiscalização socioambiental especialmente em relação a observação ecoturística da fauna marinha. Os resultados mostram a necessidade urgente de um inventário das atividades comerciais de ecoturismo marinho no Brasil. É necessário conhecer as contribuições e interesses dos vários atores envolvidos no setor comercial. Para o ecoturismo marinho ser amplamente implementado comercialmente no país com sustentabilidade socioambiental é necessário superar e resolver os obstáculos já identificados.